Оцінка плавності руху колісного трактора ХТЗ-242К при впливі нерівностей поверхні - Кальченко, Борис Іванович; Кожушко, Андрій Павлович; Кісельов, Андрій Русланович (НТУ "ХПІ", 2017)
Наведено математичний опис руху підресорених мас колісного трактора ХТЗ-242К, який має ресорну підвіску. Представлено передаточну функцію підресореної маси трактора. Сформовано випадкову функцію мікропрофілю поверхні, по якій експлуатується колісний трактор при виконанні транспортних та технологічних операцій. Визначено оціночні характеристики плавності руху колісного трактора, які базуються на обчисленні значення дисперсії вертикальних переміщень та прискорень остову передньої та задньої частин трактора.

In this paper the mathematical description of motion of the submerged masses of a wheeled tractor KhTZ-242K, which has spring suspension, is given. The transmission function of the submerged mass of the tractor is presented, on the basis of which the displacements and accelerations of the front and rear parts of the tractor frame are determined. A random function of the microprofile of the surface (asphalt concrete, ground and spherical spike cultures) on which the wheeled tractor is used during transport and technological operations is formed. The estimation characteristics of the smoothness of motion of the wheeled tractor are determined based on the calculation of the value of the dispersion of vertical displacements and acceleration of the front and rear parts of the tractor frame.
Keywords: коливання остову; передаточна функція; мікропрофіль; рівняння Лагранжа; tractor; oscillation of body; suspension function; microprofile; smoothness of motion